PENGARUH KOMPRES AIR REBUSAN JAHE MERAH TERHADAP PENURUNAN NYERI OSTEOARTHRITIS PADA LANSIA - Raden Ayu Dhiyaa Ardelia; Nurjannah (LPPM STIKes Mitra Adiguna, 2025)
Osteoarthritis is one of the most common types of arthritis, this degenerative joint condition causes pain, swelling and stiffness, affecting a person's ability to move freely. Osteoarthritis attacks all joints, including the surrounding tissue and most often occurs in the knees, hips, spine and hands. The aim of this study was to determine the intensity of osteoarthritis pain in the elderly before and after giving a compress made of boiled red ginger water. This research uses a One Group Pre-Test and Post-Test Design. The sampling technique used was purposive sampling so that the number of respondents was 52 respondents. Analysis used the Wilcoxon test with the results of the analysis showing that there was a significant influence or difference in the increase in the average value of the osteoarthritis pain scale in the elderly before the red ginger boiled water compress was applied and after the red ginger boiled water compress was applied (p-value = 0.000). It is hoped that community health centers can implement red ginger boiled water compresses which can reduce osteoarthritis pain in the elderly as a complementary therapy.